A contemporary concept of monetary sovereignty - Zimmermann, CD (2011)
This thesis analyses whether the concept of monetary sovereignty evolves under the impact of globalization and financial integration, and provides a framework for assessing what this implies. Thereby, this thesis contributes to a better understanding of both the contemporary exercise of sovereign powers in monetary and financial matters and of the driving forces behind the evolution of international law in this field. As elaborated in chapter 1, the contemporary concept of monetary sovereignty proposed by this thesis is not static but dynamic in nature. Due to the dual nature of sovereignty as a concept having not only positive but also important normative components, monetary sovereignty cannot become eroded under the impact of legal and economic constraints. Chapter 2 examines the ongoing hybridization of international monetary law arising from changes in the sources of this complex body of law, from the unsuitability of the categories of ‘hard’ and ‘soft’ law for characterizing all normative evolutions in this field, and from the rise of private and transnational monetary law. Chapter 3 scrutinizes the phenomenon of exchange rate misalignment under monetary and trade law. Intrinsically related, it assesses which aspects of the IMF’s legal framework should be reformed in order to tackle contemporary challenges to the stability of the international monetary system, such as global current account imbalances. Chapter 4 analyses the increasing regionalization of monetary sovereignty. It argues that, to the extent that transferring sovereign powers to a monetary union is what provides a state’s population with maximum monetary and financial stability, the underlying transfers are not a surrender of monetary sovereignty, but its effective exercise under the form of cooperative sovereignty. Finally, chapter 5 assesses the implications of the contemporary concept of monetary sovereignty proposed herein for the reorganization of the international financial architecture in the wake of the Great Recession.